E-coli Bacterial Pollution Test Results in Mineral Water As a Learning Media for Electronic Practicum Instructions - Habibatur Rohmah; Ospa Pea Yuanita Meishanti (APPLICATION: Applied science in Learning Research, 2021)
The contamination test determines the microbiological contamination contained, does not exceed the limit of provisions to be able to determine the quality and safety of raw materials, because high microbiological contamination can endanger health. An example of microbiology is the bacterium Eschericia coli. E-coli is usually found in the feces of living things carried by the flow of water sources until it is absorbed by the soil. If the water source is used as drinking water by the community without going through a processing process and still contains e-coli bacteria. In this modern era, information is easily obtained through online and in the learning process. Learning will be more interesting if the learning media presented are varied. The following research is a development research that aims to determine the feasibility of electronic practicum instruction media. Media development uses a 4D model, with quantitative research data types obtained from scores and qualitative data obtained from suggestions. The results obtained from media experts are 84% Very Worthy, while material experts are 75% with proper criteria. The results obtained indicate that the media is feasible to be developed.